Velocity specificity of heavy weight training for kayak sprint performance - Liow, D. K.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 1998)
Experienced male and female kayakers (N = 39) were matched by sex and sprint time and randomly assigned to a slow weight training, explosive weight training, or control (normal training) group. Weight training using sport-specific exercises was performed twice a week for six weeks. Possible effects were measured by having Ss sprint 15 m. It was found that at the very start, when movements were slow, the slow-training group improved most (6.9%), the fast group next (3.2%), and the control group least (1.4%). Over the last 3.75 m the fast training group improved most (3.0%), the slow group next by (2.1%), and the control least (-0.8%). Implication: Slow weight training exercises train one to respond best when moving slow. Fast weight training exercises train athletes to respond best when moving fast. However, both forms of training improve performances better than no weight-training.